IMPLEMENTASI WEBSITE SEBAGAI MEDIA PROMOSI DAN INFORMASI PADA MAX Team OUTBOUND TRAINING UNTUK MEMUDAHKAN DAN MENINGKATKAN DAYA TARIK PELANGGAN - hendri rasminto; Danang Danang (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2018)
Abstract The development of computer and internet science has covered the world community today. including companies and agencies around the world have internet facilities and websites as a form of promotion to the public. Likewise with MAX team Outbound Training Semarang, which continues to strive for improvement in its promotion program. To be able to provide convenience in promotional activities on MAX team requires a media campaign that is fast and can be accessed by the wider community. In this study concluded that the ease of accessing the website is very good, namely 81.67%. In addition, the attractiveness of consumers in accessing products online is also getting better, reaching 78.9%.